Postzygotic mosaicism in basal cell naevus syndrome. (1st July 2017) - Reinders, M.G.H.C.; Boersma, H.J.; Leter, E.M.; Vreeburg, M.; Paulussen, A.D.C.; Arits, A.H.M.M.; Roemen, G.M.J.M.; Speel, E.J.M.; Steijlen, P.M.; van Geel, M.; Mosterd, K.
Summary: Basal cell naevus syndrome (BCNS) is an autosomal dominant disorder most commonly caused by a germline mutation in the Drosophila homologue of patched‐1 gene ( PTCH1 ). Here we describe a patient with clinical signs of BCNS, caused by postzygotic mosaicism of a PTCH1 mutation. We performed restriction fragment length polymorphism analysis and Droplet Digital polymerase chain reaction to determine the degree of mosaicism in different tissues of this patient. Our case shows that a relatively low‐grade mosaicism can lead to clinical signs reminiscent of those caused by a germline mutation. This finding has important implications for genetic counselling and therefore is pivotal to recognize for dermatologists, as well as for clinical geneticists and clinical laboratory geneticists.